Pengaruh Good Corporate Governance terhadap Nilai Perusahaan - Ika Faradilla Purwaningrum; Tantina Haryati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This research aims to test and analyze the influence of Good Corporate Governance including institutional ownership, managerial ownership, an independent board of commissioners, and an audit committee on the value of the company. The population used in this study is a State-Owned Enterprise (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020. This type of research is explanatory research with a quantitative approach. The data used in this study is secondary data in the form of annual reports. Sampling techniques are obtained using purposive sampling methods. Based on predetermined criteria, 14 state-owned enterprises (SOEs) were obtained as research samples. The analysis technique used in this study is Partial Least Square (PLS) with the help of the SmartPLS program. The results of this study show that Institutional Ownership has a positive and significant effect on the value of the company, Managerial Ownership has a positive and significant effect on the value of the company, the Independent Board of Commissioners has no significant effect on the value of the company, the Audit Committee has a positive and significant effect on the value of the company. Keywords: Institutional Ownership; Managerial Ownership; Independent Board of Commissioners; Audit Committee; Company Value.